More than meets the eye : revealing the complexities of an interpreted education - Smith, Melissa B. (Washington, DC : Gallaudet University Press, 2013)
Sign language interpreters often offer the primary avenue of access for deaf and hard of hearing students in public schools. More than 80% of all deaf children today are mainstreamed, and few of their teachers sign well enough to provide them with full access. As a result, many K-12 interpreters perform multiple roles beyond interpreting. Yet, very little is known about what they actually do and what factors inform their moment-to-moment decisions. This volume presents the range of activities and responsibilities performed by educational interpreters, and illuminates what they consider when making decisions.
"Sign language interpreters often offer the primary avenue of access for deaf and hard of hearing students in public schools. More than 80% of all deaf children today are mainstreamed, and few of their teachers sign well enough to provide them with full access. As a result, many K-12 interpreters perform multiple roles beyond interpreting. Yet, very little is known about what they actually do and what factors inform their moment-to-moment decisions. This volume presents the range of activities and responsibilities performed by educational interpreters, and illuminates what they consider when making decisions.To learn about the roles of K-12 interpreters, author Melissa B. Smith conducted in-depth analyses at three different schools. She learned that in response to what interpreters feel that their deaf students need, many focus on three key areas: 1) visual access, 2) language and learning, and 3) social and academic participation/inclusion. To best serve their deaf students in these contexts, they perform five critical functions: they assess and respond to the needs and abilities of deaf students; they interpret with or without modification as they deem appropriate; they capitalize on available resources; they rely on interactions with teachers and students to inform their choices; and they take on additional responsibilities as the need arises." -- Publisher's description.
At first glance : taking a look at deaf education and interpreting in K-12 classrooms -- As previously seen : interpreting in schools -- Examining the work of interpreters through multiple lenses -- Scenes and subjects -- Opening our eyes : discovering what interpreters do and why -- What remains to be seen -- List of categories and definitions for coding video data -- Expanded list and definitions of what and why categories -- Overarching themes from interview and video data.
Includes bibliographical references (p. 187-195) and index.
Keywords: Deaf students; Deaf children -- Education; Interpreters for the deaf; Teachers of the deaf; Deaf children -- Education; Deaf students; Interpreters for the deaf; Teachers of the deaf